The Role of Geographer and Natural Scientist Henri Francois Pittier (1857-1950) in the Evolution of Geography as a Science in Costa Rica - Yacher, Leon I. (Mellen studies in geography ; v. 12, 2004)
Keywords: Costa Rica; History; History; Geography; Influence; Geography; Latin America; Pittier, Henri, 1857-1950; award_winner; dept.egm

Jaltomata andersonii (Solanaceae): A new species of Peru - Mione, T.; Leiva G., S.; Yacher, L. (Rhodora, 2004)
Jaltomata andersonii (Solanaceae), here named, is distributed on the western slope of the Andes, in the Departments of Ancash and Lima, Peru, from 2300 to 3400 m of elevation. This species differs from others of the genus by having an unarticulated axis connecting the flower to the plant where all others have both a peduncle and a pedicel. The following combination of features also characterize this species: the hairs of leaves and axes are gland-tipped; the petiole is no longer than 1 cm; the flowers are solitary; the corolla is broadly crateriform-rotate, purple, and up to 3.7 cm in diameter; and the filaments are extremely villous at their bases.
Keywords: Andes; Corolla; Flora of Peru; Jaltomata; Jaltomata andersonii; Magnoliophyta; Solanaceae; dept.egm; ⛔ No DOI found